Refugees and Space in Polish Literary Reportages. The Refugee Camp as a Space of the State of Exception, Bare Town and Non-Place - Zawisza, Agnieszka (Porównania, 2025)
The article aimed to examine how Polish literary reportage presents the space of refugee camps. The analyzed books were Kontener by Katarzyna Boni and Wojciech Tochman (2014) and Najważniejszy wrzesień świata. Kronika niezauważonego ludobójstwa na Rohingach by Marek Rabij (2019). The key interpretative categories used in the analysis of the space of refugee camps were the space of the state of exception by Giorgio Agamben, the bare town by Michel Agier, and the non-place by Michel Augé.